Na rota dos calçados : a Vulcabrás Azaléia em Sergipe. Um estudo das transformações no mundo do trabalho - Reis, Igor Macedo (2016)
This work aimed to analyze the mobility of the shoe company Vulcabrás Azaleia, its historical origin and its development until the arrival in Sergipe and the closure of three of its four plants in the state (Carira, Lagarto and Ribeirópolis). We examine the changes in the labor market and the extent to which they corresponded (or not) for the expansion and retraction of the footwear industry in Sergipe. Theoretical issues discussed included: an analysis of class work; forms of production relation, with Fordism and the "flexible accumulation" as analysis parameters. In addition, we made use of analytical category Structural Crisis developed by István Mészáros, which enabled us to understand why the closure of factories and consequently unemployment that reached Azaleia workers inside Sergipe. It is a qualitative research, carried out through semi-structured interviews, field notes and documentary research that enabled the construction of empirical corpus, in which we highlight some results: political demobilization; socio-economic impacts; formation of a working class just to leave the field. Concluding that the mobility of capital economically enhances areas where the industry did not exist, and at the same time founded a mass of workers increasingly precarious, by factors of its own genesis as the lack of a union tradition, low contingent education and state aid to developers of policies for private capital to the detriment of the interests of workers.